ANALISIS TINGKAT LIKUIDITAS PT. SEPATU BATA TBK DITINJAU DARI PERPUTARAN KAS DAN MODAL KERJA - Ade Ratna Sari; Mahadi Saputra; Nadiah Oktavia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Getting a profit is a business goal, so every effort is made, including controlling finances. Liquidity is one of the financial parameters, which explains how smooth internal finance is, so that it can finance business activities and obligations. This study aims to reveal information related to the liquidity of a company by looking at cash rotation and working capital. For this reason, quantitative methods are used with secondary data (financial reports) as the unit of analysis. In describing the data, regression analysis was used. The results showed that the level of liquidity was highly dependent on cash and working capital. Statistically, working capital is the dominant factor in corporate liquidity. This confirms that liquidity is an alternating flow whose main source is capital. This means that the company's business activities will run smoothly if supported by large capital, this has an impact on the smooth flow of the company's cash flow. This triggers high levels of income, and helps the company cope with its obligations